Exploring the Experience of Nursing Students in Performing Cardiopulmonary Resuscitation (CPR) in Manambai Hospital: A Qualitative Study - Purwadi, Hendri; Harmili, Harmili; Friansyah, Kemas Andika (Ahmar Metastasis Health Journal, 2024)
In hospital cardiac arrest (IHCA) is a worldwide issue due to its low survival rate with survival rate decreases by 10% every minute in the absence of cardiopulmonary resuscitation (CPR). All medical staff who are providing care to patients, including nursing students, must immediately begin CPR and call for an activated advanced medical team. With less experience, nursing students find it challenging and demanding to perform high-quality CPR. This study aims to explore the nursing student experience in providing CPR to the patient at the hospital. This study was a qualitative design with a phenomenological approach. An in-depth interview with a semi-structural approach was conducted among 10 nursing students at the Manambai hospital. The data analysis used Colaizzi's (1978) seven-step method. The result shows that three themes were identified,regarding nursing stedent experience in performing CPR including : nursing students’ feelings (fear, worry, satisfaction, fearfulness, pride, and stress), challenges (difficulty recognising the difference between real patients and CPR training manikin, and difficulty following certain medical personnel's CPR performance), and the need for feedback from senior medical staff and clinical instructors. The conclusion is nursing students need more practice and opportunities to perform CPR under the supervision of  lecturers and clinical instructors in order to provide excellent and safe patient care. Clinical instructors (CI)  should provide additional opportunities for CPR under CI supervision. Moreover, in order to improve nursing students' CPR abilities and knowledge, lecturers should improve high-fidelity simulation.